Rozwiąż równiania:
a) (5-x):2-(2x+5)=2x-1
b)(x-1):3+5(x+3)=2-x
c) 2(2x+7)-(x-2):5=9+2x
d)-2(3x+10)-(x+8):4=3(x+5)
e)3+(8+x):2=2x-1
f)2x-(3x-7):4=3x-1
g)5-(x+5):3=2-x
h)3x+(4-x):5=z-1
i)5(3-x)+(x-3)=4x+5
j)4(x-1)+(2x-1)=3x-1
k)2(5-x)-(7-x)=x-1
l)3(2x-7)-(2x-4)=5-x

2

Odpowiedzi

2010-01-20T21:46:00+01:00
A) (5-x):2-(2x+5)=2x-1 /*2
5-x-4x-10=4x-2
-5x-4x=-2+10-5
-9x=3 /:(-9)
x=-⅓

b)(x-1):3+5(x+3)=2-x /*3
x-1+15x+45=6-3x
16x+3x=6-44
19x=-38 /:19
x=-2

c) 2(2x+7)-(x-2):5=9+2x /*5
20x+70-x+2=45+10x
19x-10x=45-72
9x=-27 /:9
x=-3

d)-2(3x+10)-(x+8):4=3(x+5) /*4
-8(3x+10)-(x+8)=12(x+5)
-24x-80 -x-8=12x+60
-25x-12x=60+88
-37x=148 /:(-37)
x=-4

e)3+(8+x):2=2x-1 /*2
6+8+x=4x-2
x-4x=-2-14
-3x=-16 /:(-3)
x=16/3
x=5⅓

f)2x-(3x-7):4=3x-1 /*4
8x-3x+7=12x-4
5x-12x=-4-7
-7x=-11 /:(-7)
x=11/7

g)5-(x+5):3=2-x /*3
15-x-5=6-3x
-x+3x=6-10
2x=-4 /:2
x=-2

h)3x+(4-x):5=x-1 /*5
15x+4-x=5x-5
14x-5x=-5-4
9x=-9 /:9
x=-1

i)5(3-x)+(x-3)=4x+5
15-5x+x-3=4x+5
-4x-4x=5-12
-8x=-7 /:(-8)
x=7/8

j)4(x-1)+(2x-1)=3x-1
4x-4+2x-1=3x-1
6x-3x=-1+5
3x=4 /:3
x=4/3

k)2(5-x)-(7-x)=x-1
10-2x-7+x=x-1
-x-x=-1-3
-2x=-4 /:(-2)
x=2

l)3(2x-7)-(2x-4)=5-x
6x-21-2x+4=5-x
4x+x=5+17
5x=22 /:5
x=4,4
2010-01-20T22:01:46+01:00
A) (5-x):2-(2x+5)=2x-1
5/2-x/2-2x-5=2x-1|*2
5-x-4x-10=4x-2
-9x=3|:(-9)
x= -1/3
b)(x-1):3+5(x+3)=2-x
x/3-1/3+5x+15=2-x|*3
x-1+15x+45=6-3x
19x= -38|:19
x= -2
c) 2(2x+7)-(x-2):5=9+2x
4x+14-x/5+2/5=9+2x|*5
20x+70-x+2=45+10x
9x= -27|:9
x= -3
d)-2(3x+10)-(x+8):4=3(x+5)
-6x-20-x/4-8/4=3x+15|*4
-24x-80-x-8=12x+60
-37x=148|:(-37)
x= -4
e)3+(8+x):2=2x-1
3+8/2+x/2=2x-1|*2
6+8+x=4x-2
-3x=-16|:(-3)
x=5i1/3
f)2x-(3x-7):4=3x-1
2x-3x/4+7/4=3x-1|*4
8x-3x+7=12x-4
-7x=-11|:(-7)
x=1i 4/7
g)5-(x+5):3=2-x
5-x/3-5/3=2-x|*3
15-x-5=6-3x
2x=-4|:2
x= -2
h)3x+(4-x):5=z-1
3x+4/5-x/5=x-1|*5
15x+4+x=5x-5
11x=-9|:11
x= - 9/11
i)5(3-x)+(x-3)=4x+5
15-5x+x-3=4x+5
-8x=-7|(-8)
x=7/8
j)4(x-1)+(2x-1)=3x-1
4x-4+2x-1=3x-1
3x=4|:3
x=1i1/3
k)2(5-x)-(7-x)=x-1
10-2x-7+x=x-1
-2x=-4|:(-2)
x=2
l)3(2x-7)-(2x-4)=5-x
6x-27-2x+4=5-x
5x=28|:5
x=5i3/5